Chiral Discrimination by Ionic Liquids: Impact of Ionic Solutes. Issue 4 (26th February 2015) - Brown, Christopher J.; Hopkins, Todd A.
Abstract Chiral ionic liquids hold promise in many asymmetric applications. This study explores the impact of ionic solutes on the chiral discrimination of five amino acid methyl ester‐based ionic liquids, including L‐ and D‐alanine methyl ester, L‐proline methyl ester, L‐leucine methyl ester, and L‐valine methyl ester cations combined with bis(trifluoromethanesulfonimide) anion. Circularly polarized luminescence spectroscopy was used to study the chiral discrimination by measuring the racemization equilibrium of a dissymmetric europium complex, Eu(dpa)33− (where dpa = 2, 6‐pyridinedicarboxylate). The chiral discrimination measured was dependent on the concentration of Eu(dpa)33− and this concentration‐dependence was different in each of the ionic liquids. Ionic liquids with L‐leucine methyl ester and L‐valine methyl ester even switched enantiomeric preference based on the solute concentration. Changing the cation of the Eu(dpa)33− salt from tetrabutylammonium to tetramethylammonium ion also affected the chiral discrimination demonstrated by the ionic liquids. Chirality 27:320–325, 2015. © 2015 Wiley Periodicals, Inc.